Technology of Sweet Vegetable Semi-Finished Products - Ashurova M. Z.; Sulaymanova G. X. (International Journal on Orange Technologies, 2021)
Questions about the technological properties of vegetables, in particular, as stabilizers, emulsion and foam structure of food are considered. The data on the use of vegetables for the production of sweet dishes and the improvement of technology, as well as increasing the nutritional value of flour products are presented.